TRANSFORMATION OF REFERENCE AND BIBLIOGRAPHY OF THE LIBRARY APPARATUS AS A MEANS OF INCREASING EFFICIENCY OF HER WORK (Pedagogy of Higher and Secondary Education, 2007)
Some basic components and the transformation of informative and bibliographical librarian apparatus in higher educational establishments are considered here. The significance of computerization as a means of increasing the efficiency of work of libraries is emphasized.